2013
DOI: 10.1007/s00213-013-3090-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol attenuates amygdala–frontal connectivity during processing social signals in heavy social drinkers

Abstract: Rationale Convergent evidence shows that alcohol exerts its effects on social behavior via modulation of amygdala reactivity to affective stimuli. Given that affective processing involves dynamic interactions between the amygdala and the prefrontal cortex (PFC), alcohol's effects are likely to extend beyond regional changes in brain activity to changes that manifest on a broader functional circuit level. Objective The current study examines alcohol's effects on functional connectivity (i.e., ‘coupling’) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 123 publications
(155 reference statements)
2
50
0
Order By: Relevance
“…Participants were told that the study was investigating the effects of drugs and pictures on mood, and to minimize drug expectancies they were told they could receive one of the following: stimulant, sedative, alcohol, or placebo (Conrad et al, 2012;Gorka et al, 2013;King et al, 2014). They were instructed to consume their normal amounts of caffeine and nicotine but to abstain from drugs, including alcohol, for 24 hours before each session, and to not consume any food after 9 A.M.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were told that the study was investigating the effects of drugs and pictures on mood, and to minimize drug expectancies they were told they could receive one of the following: stimulant, sedative, alcohol, or placebo (Conrad et al, 2012;Gorka et al, 2013;King et al, 2014). They were instructed to consume their normal amounts of caffeine and nicotine but to abstain from drugs, including alcohol, for 24 hours before each session, and to not consume any food after 9 A.M.…”
Section: Methodsmentioning
confidence: 99%
“…Aggressive behavior has also been linked to PFC hypo-activation, especially in the dorsal (d) ACC (Sterzer et al, 2005;Meyer-Lindenberg et al, 2006;Aharoni et al, 2013), and to increased activation of the amygdala, in particular for impulsive aggression triggered by provocation or threat, also referred to as reactive aggression (Meyer-Lindenberg et al, 2006;Coccaro et al, 2007). Reduced functional PFC-amygdala coupling under alcohol (Gorka et al, 2013) further suggests that alcohol-induced aggression might be mediated by impaired PFC functioning under alcohol, which might indirectly increase activation of the amygdala (Heinz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In an fMRI study examining the acute effect of alcohol in 12 heavy but non-dependent social drinkers (greater than or equal to 10 alcoholic drinks per week and one to five weekly binge-drinking episodes), participants displayed reduced amygdalar activity to fearful and angry faces after the ingestion of alcoholic beverages compared with the placebo session (Sripada et al, 2011). Using the same data set, this group additionally found that the functional connectivity of the amygdala was decreased in the right OFC during the viewing of angry and fearful faces and in the left OFC during the viewing of happy faces following the acute ingestion of alcohol (Gorka et al, 2013). This result is consistent with a previous report that an intravenous injection of alcohol decreases limbic brain response to fearful faces in healthy individuals (Gilman et al, 2008).…”
Section: Acute Effects Of Alcohol On the Prefrontal-limbic-striatal Cmentioning
confidence: 80%
“…Several fMRI studies have reported that alcohol attenuates emotional response to aversive or threat-related stimuli via its influence on limbic regions (Gilman et al, 2008;Gorka, Fitzgerald, King, & Phan, 2013;Sripada et al, 2011). In an fMRI study examining the acute effect of alcohol in 12 heavy but non-dependent social drinkers (greater than or equal to 10 alcoholic drinks per week and one to five weekly binge-drinking episodes), participants displayed reduced amygdalar activity to fearful and angry faces after the ingestion of alcoholic beverages compared with the placebo session (Sripada et al, 2011).…”
Section: Acute Effects Of Alcohol On the Prefrontal-limbic-striatal Cmentioning
confidence: 97%